2011
DOI: 10.1007/978-3-642-25775-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Animated Faces for Robotic Heads: Gaze and Beyond

Abstract: Abstract. We introduce an approach to using animated faces for robotics where a static physical object is used as a projection surface for an animation. The talking head is projected onto a 3D physical head model. In this chapter we discuss the different benefits this approach adds over mechanical heads. After that, we investigate a phenomenon commonly referred to as the Mona Lisa gaze effect. This effect results from the use of 2D surfaces to display 3D images and causes the gaze of a portrait to seemingly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Susumu Tachi's TELESAR project uses humanoid animatronic robot surrogates with retro-reflective surfaces showing the remote inhabiter through autostereoscopic projection [11]. Al Moubayed et al projected animated human faces onto a 3D physical head, and investigated the perceived gaze direction [12]. In particular, they showed that the 3D model resulted in an accurate perception of gaze direction, unlike the Mona Lisa gaze effect typically seen when using a 2D surface to display 3D face imagery.…”
Section: Related Workmentioning
confidence: 99%
“…Susumu Tachi's TELESAR project uses humanoid animatronic robot surrogates with retro-reflective surfaces showing the remote inhabiter through autostereoscopic projection [11]. Al Moubayed et al projected animated human faces onto a 3D physical head, and investigated the perceived gaze direction [12]. In particular, they showed that the 3D model resulted in an accurate perception of gaze direction, unlike the Mona Lisa gaze effect typically seen when using a 2D surface to display 3D face imagery.…”
Section: Related Workmentioning
confidence: 99%